Open-source delay discounting assessment software: Development and usability - Utsumi, Daniel Augusto; Gasi, Rogério Tavares; Miranda, Mônica Carolina; Querino, Emanuel Henrique Gonçalves; Pompéia, Sabine (Behavior research methods, 2025)
Delay discounting (DD) describes the tendency of individuals to devalue the worth of a reward as a function of the delay in receiving it. DD is impaired in many clinical conditions and changes across development. Many existing automated DD tasks are built on copyrighted software and primarily designed for English speakers, which hinders content editing and accessibility. Given this scenario, we had three objectives: (1) to develop open-source DD software named the “Waiting Game” with a user interface (UI) that is easily editable (regarding language, reward type/magnitude and delay duration) via an Excel spreadsheet, and provides automated DD scoring; (2) to create a comprehensive manual (User Guide) to accompany the software; and (3) to assess the software’s usability and the clarity of the manual through an online questionnaire completed by experts in cognitive assessment. The software was developed using game design and encompasses three tasks that assess DD under three conditions: (1) hypothetical delays (waiting is imagined) and no real rewards (only points) are gained); (2) real delays (waiting is necessary) and real rewards gained; and (3) real delays and hypothetical rewards. An expert evaluation using the System Usability Scale and the International Test Commission recommendations confirmed the software’s suitability. Minor changes were made to the User Guide and UI based on the expert feedback. We conclude that the Waiting Game offers a valid, cost-free, and automated solution for DD assessment that facilitates reward and delay manipulations in hypothetical/real delay and reward paradigms across diverse sociocultural contexts.